x y z = y z x = z x y x^{\frac{y}{z}} = y^{\frac{z}{x}} = z^{\frac{x}{y}}

Algebra Level 3

x y z = y z x = z x y for x , y , z > 0 x^{\frac{y}{z}} = y^{\frac{z}{x}} = z^{\frac{x}{y}} \,\text{for} \,\,x,y,z>0

What are the solutions to the above equation?

x = y = z x=y=z and some other finitely many solutions x = y = z x=y=z only x = y = z x=y=z and some other infinitely many solutions

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Levi Walker
Oct 27, 2018

Raising everything to the power of x y z xyz gives us x x y 2 = y y z 2 = z z x 2 x^{xy^{2}} = y^{yz^{2}} = z^{zx^{2}} x = y = z x=y=z is a solution since x x 3 = x x 3 = x x 3 x^{x^{3}} = x^{x^{3}} = x^{x^{3}} However, x = y z x=y \neq z cannot be a solution. To show this, let's first assume that it provides a solution. We then get x x 3 = x x z 2 = z z x 2 x^{x^{3}} = x^{xz^{2}} = z^{zx^{2}} Equating the exponents on the first two sides gives x 3 = x z 2 x^{3} = xz^{2} , or z = ± x z = \pm x . z = x z = - x cannot hold because all numbers must be nonzero, while z = x z = x contradicts our condition that x z x \neq z . Thus, x = y z x=y \neq z can never solve this equation.

Hana Wehbi
Nov 12, 2018

Nice problem.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...